Kontribusi Agroforestri Terhadap Pendapatan Rumah Tangga Petani (Studi Kasus Kecamatan Simpang Kanan Kabupaten Rokan Hilir) - Muh Arisandi; M. Mardhiansyah; Viny Volcherina Darlis (Jurnal Online Mahasiswa (JOM) Bidang Pertanian, 2021)
Agroforestry is land management system aims to overcome a problem of availability on land and increase land productivity. The community in Simpang Kanan sub-district, Rokan Hilir district, has practiced an agroforestry system with a mixed garden pattern, selecting plant types on the agroforestry land to get higher yields or increase income. Mixed gardens practiced by farmers are gardens with diverse types of crops. The types of forestry plants developed by the farmers include mangosteen, durian, pasak bumi, meranti, kulim, mahang and other types of forestry plants. As for non-forestry crops, the farmers chose agricultural crops such as secondary crops and plantation crops such as oil palm. The purpose of this study was to determine the components of agroforestry in Simpang Kanan Subdistrict, Rokan Hilir Regency and to find out the contribution of agroforestry in Simpang Kanan Subdistrict, Rokan Hilir Regency to farmers' income. This research uses observation method, survey method and literature study. Observation method is carried out by direct observation of the research object, survey method data is collected by conducting direct interviews with agroforestry land owners and literature studies are obtained by studying literature, reports, scientific works, research results, and other sources related to research. Data analysis was carried out in a quantitative descriptive manner based on the results of observations that had been made. The results of this study found 3 types of basic components of agroforestry land owned by farmers. The constituent components are forestry plants as many as 16 species and 125 trees, agricultural plants found as many as 9 species and plantation crops namely oil palm plantations. Total income from agroforestry business is Rp. 57,418,500/year. This value contributes 48% of the total income of farmers. Keyword: agroforestry, contribution, revenue, composition.